PENGUASAAN TANAH TANPA HAK DI KOTA JAMBI : (Studi Kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013) - Kelvin Alfarisi Alkap (Universitas Jambi, Fakultas Hukum, 2022)
This study aims to determine and analyze the factors that cause land tenure without rights in Jambi City in the case of the Supreme Court Decision Number 1935 K/Pdt/2013 and the legal consequences of land tenure without rights in Jambi City in the case of the Supreme Court Decision Number 1935 K/Pdt. /2013. The formulation of the problems raised are 1) what are the factors that cause land tenure without rights in Jambi City in the case of the Supreme Court Decision Number 1935 K/Pdt/2013; 2). what are the legal consequences of land tenure without rights in Jambi City in the case of the Supreme Court's Decision Number 1935 K/Pdt/2013. The method used is the type of empirical juridical research. The results of the study show that 1) the factors that can cause land tenure without rights in the case of the Supreme Court Decision Number 1935 K/Pdt/2013 is an error in object. Farida Wan Hamid and the other defendants own the object of the case based on a grant from Defendant II as proof of ownership, namely Certificate of Ownership Number 511 dated July 11, 1972, issued by Defendant III, Jambi City Land Office; 2) land tenure without rights in the case of the Supreme Court's Decision Number 1935 K/Pdt/2013, is classified as an act against the law so that the actions of the party who did it can be filed in a civil lawsuit to ask for a sum of money for compensation. ABSTRAK Penelitian ini bertujuanuntuk mengetahui dan menganalisis faktor yang menyebabkan terjadinya penguasaan tanah tanpa hak di Kota Jambi pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013 dan akibat hukum penguasaan tanah tanpa hak di Kota Jambi pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013.Perumusan masalah yang diangkat yaitu 1) apa saja faktor yang menyebabkan terjadinya penguasaan tanah tanpa hak di Kota Jambi pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013; 2). bagaimanaakibat hukum penguasaan tanah tanpa hak di Kota Jambi pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013. Metode yang digunakan adalah tipe penelitian yuridis empiris. Hasil penelitian menunjukkan bahwa 1) faktor yang bisa menyebabkan terjadinya penguasaan tanah tanpa hak pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013 adalah keinginan untuk memiliki yang tinggi, disertai dengan adanya niat dan kesempatan untuk menguasai tanah yang jelas bukan miliknya; 2) penguasaan tanah tanpa hak pada kasus Putusan Mahkamah Agung Nomor 1935 K/Pdt/2013, digolongkan sebagai perbuatan melawan hukum sehingga tindakan pihak yang melakukannya dapat dilakukan gugatan secara pidana, pihak keluarga juga dapat mengajukan gugatan secara perdata untuk meminta sejumlah uang ganti rugi.